Joey Pigza loses control - Gantos, Jack. (London : Corgi Yearling, 2001)
If people think Joey Pigza has problems, they should meet his dad ! When Joey gets to spend the summer with him, he soon finds out why Mom was so worried... Can Joey live life his dad's way or will the chaos take over?
Keywords: Comedy -- Fiction; Families -- Fiction